Phytochemical, Antioxidant, and Antibacterial Activity of Essential Oil Hyptis capitata Using Solvent-Free Microwave Extraction - Susanti, Yuni; A’yun, Ayu Qurota (Journal of Applied Agricultural Science and Technology, 2024)
Knobweed (Hyptis capitata) is a member of the genus Hyptis and the medicinal properties remain underexplored in scientific research. In this context, the use of Hyptis capitata essential oil as a medicinal plant depends on phytochemical content. Hyptis capitata is easily found in rice fields or agricultural areas such as Banyuwangi. Therefore, this research aimed to describe phytochemical compounds, antioxidants, and antibacterial activity of essential oil Hyptis capitata in Banyuwangi using Solvent-Free Microwave Extraction (SFME) method. Essential oil from leaves and inflorescence of the species was obtained with a yield of 0.273% and 0.282%, respectively. The results of Gas Chromatography-Mass Spectrometry (GC-MS) analysis showed that inflorescence and leaves of Hyptis capitata consisted of diterpenes, triterpenes, sesquiterpenes, esters, alcohols, ketones, and other groups of compounds. SFME method for the extraction affected both essential oil yield and phytochemical composition. Meanwhile, there were variations in phytochemical compounds of the plant parts used and from several previous research. The optimum % DPPH inhibition value of leaves extract and inflorescence were 19.187±0,06% and 18.784±0,06%, respectively. Antibacterial activity against Staphylococcus aureus and Eschericia coli reported no inhibition of plant extract. Phytochemical analysis showed several compounds with antibacterial potential, suggesting the need for further research of antibacterial activity against other pathogenic bacteria and exploration of additional biological activities.